Job Satisfaction among Eye Health Care Provider at Lumbini Eye Institute and Research Center, Bhairahawa, Nepal - Thapa, Saraswati Khadka; KC, Sudeep (Journal of Bharatpur Hospital, 2025)
Background Job satisfaction is a major factor affecting employee performance, loyalty, and the overall effectiveness of an organization. It is influenced by factors such as salary, promotion, recognition & reward, training & development. Satisfied employees tend to show greater dedication and deliver higher performance in their roles. Survey was conducted to assess the level of job satisfaction and the determinants of job satisfaction among the employees working at Lumbini Eye Institute and Research Centre. Methods This study utilized a cross-sectional survey design to evaluate job satisfaction among employees. Among 194 eligible participants 91.24% responded in the survey. Survey administered schedule and questionnaire as per convenience of the participants. Questionnaire included - Likert scale (Strongly agree, agree, Neutral, disagree and strongly disagree), rating scale and open-ended questions. Third-party surveyor was appointed to facilitate the data collection. Results Employees express high level of engagement, supervisor support and institutional pride but notable concern regarding recognition, promotion fairness, training and feedback mechanism. Among the respondents 65% felt satisfied, 27% remained average and 8% expressed dissatisfied with their work. Conclusions The overall employee satisfaction level shows some positive sentiment; however, the presence of dissatisfaction indicates the need for improvement areas such as salary, promotion, training opportunities, work environments, and support for future career goals. The future is recommended to understand the reasons behind dissatisfaction, despite employees expressing high level of pride to work at the institute.